ديداكتيك اللغة العربية و مشاريع الإ (Didactic of the Arabic language and Reform Projects) - (Laila Balkhayr), ليلى بلخير (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: يعد تراجع تداول اللغة الفصحى، من أكبر المشكلات التي يعاني منها طلبة أقسام اللغة العربية، ومكمن الخطورة يتعزز، ما دام المجال اللغوي هو العصب المحرك لكل المجالات المعرفية الأخرى، وأي إخلال له مضاعفاته على التحصيل العلمي للطلاب، والمسار المهني المستقبلي الذي بالتأكيد يتطلب كفاءة لغوية عالية. وهذه هي الحلقة المفقودة في المنظومة التربوية، من المراحل التعليمية الدنيا، إلى المرحلة الجامعية العليا. وهناك تساؤلات عن طرائق تعليم اللغة العربية، وضعف مستوى المؤطرين القائمين بالعملية التعليمية، وعزوف المتعلمين عن تداولها. هذه الأسئلة هي المحور الذي انطلقت منه هذه الدراسة، وتكلمت عن اللغة والسياق التداولي وعلم لغة النص، وآفاق تعليمية اللغات، بعد ذلك قامت بمعالجة ظاهرة تراجع اللغة العربية بجامعة تبسة (في الجزائر) عن طريق استمارة أسئلة، مناسبة للكشف عن العوامل والأسباب. بعد تحليل الأجوبة ورصد النتائج، ومع مناقشة العوامل المؤدية لاستفحال ظاهرة الفشل اللغوي، حاولت الباحثة تقديم بعض المقترحات العلمية للخروج من هذه الأزمة. الكلمات المفتاحية:السياق التداولي-تعليمية اللغات-الكفاية الاتصالية-تداول اللغة-الثقافية. Abstract: The reduction of the classical language is considered one of the biggest problems faced by students of Arabic language departments, and where the risk is enhanced, as long as the domain of language is the main motive for all areas of knowledge, and any wrong have repercussions on the educational achievement of students, and the path of future career, which certainly requires higher efficient language. This is the missing link in the educational system, from the minimum levels of education, graduate to the stage. There are questions about the methods of teaching the Arabic language, and the low level of those who supervised the educational process, and the reluctance of learners to study the language. These questions began from the study of the established theory of this phenomenon, and talked about the language and pragmatic context, and textual discourse, and the prospects for learning languages, then the preview to study the phenomenon of decline in the Arabic language at the University of Tebessa (Algeria) by a questionnaire to explain the detection of the factors and causes. After analyzing the answers, and monitoring results, and discussing the factors leading to exacerbation of the phenomenon of the failure of language, the researcher tries to provide some scientific proposals to emerge from this crisis. Keywords: Pragmatic Context- Teaching Language- Language Skills- Language Usage- Culture. Abstrak: Kelemahan dalam menggunakan bahasa Arab fushah dianggap sebagai salah satu cabaran yang terbesar yang dihadapi oleh pelajar-pelajar bahasa Arab dan masalah ini dilihat semakin membimbangkan apabila bahasa arab fushah menjadi medium perantaraan yang utama dalam bidang-bidang ilmu yang lain. Hal ini adalah kerana ia memberi kesan kepada pencapaian akademik pelajar dan peluang kerjaya mereka di masa hadapan yang sudah pasti memerlukan mereka menguasai bahasa dengan baik dan ini merupakan kekurangan sistem pendidikan hari ini samada di peringkat rendah atau sistem pendidikan tinggi. Justeru, timbul persoalan tentang kaedah pengajaran bahasa Arab dan kelemahan tenaga pengajar dalam menjalankan proses pengajaran dan pembelajaran sehingga menyebabkan pelajar enggan bertutur dalam bahasa ini. Persoalan-persoalan ini menjadi titik tolak kepada kajian ini yang mana ia akan membincangkan tentang bahasa, konteks, analisis teks dan prospek pengajaran bahasa seterusnya menangani fenomena kemunduran bahasa Arab di Universiti Tibsah di Algeria menggunakan borang soal selidik sebagai instrumen kajian bagi mengenal pasti faktor-faktor yang berkaitan. Selepas menganalisa jawapan dan memperoleh hasil kajian tentang faktor-faktor yang membawa kepada kemunduran bahasa, penyelidik akan memberi beberapa cadangan yang sesuai bagi menyelesaikan isu ini. Kata kunci: Pragmatik – Pengajaran Bahasa – Kemahiran Bahasa – Penggunaan Bahasa – Budaya.